Production of Water-Soluble Silk Powder from Bombyx mori Linn. (Nang-Noi Srisakate 1) - Pilanee Vaithanomsat,; Chidchai Punyasawon, (Agriculture and Natural Resources, 2006)
The process for production of water-soluble silk powder from Bombyx mori Linn. (Nang-Noi Srisakate 1) was optimized. The silk cocoon was cut, dissolved in the solvent mixture at 100 °C until the homogeneity was observed. After that the solution was dialysed and centrifuged at 6,870 × g. The purified silk solution was then freeze-dried and ground into fine powder. The results showed that the mixture of MgCl2/ethanol/H2O at mole ratio of 0.8:2:8 was the most suitable solvent to completely dissolve silk fiber. The ratio of silk over dissolving solution at 10:100 (by weight) was the most appropriate ratio. Characterization of the product showed similarity to the commercial silk powder in that they were fine yellowish powder with similar amino acid profiles. However, silk powder from laboratory showed higher total nitrogen content with less percentage of ash and moisture when compared to those of the commercial product.